2003
DOI: 10.1007/s00415-003-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanisms of normal-appearing white matter damage in multiple sclerosis using diffusion tensor imaging

Abstract: Diffusion tensor imaging (DTI) investigates brain tissue microstructure in vivo. In multiple sclerosis (MS) Wallerian degeneration of axons traversing focal lesions is a potential mechanism of damage in normal-appearing white matter. In vivo evidence for this hypothesis is limited. The present study investigated the relationship between DTI-derived indices in the normal-appearing corpus callosum (CC) and the lesion loads (LLs) in connected cerebral regions. DTI was performed in 39 MS patients and in 21 age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
110
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 32 publications
17
110
0
6
Order By: Relevance
“…These studies have shown decrease of the FA values in the NAWM, probably secondary to myelin sheath and axonal destruction 4,[9][10][11] . These abnormalities tend to expand the extracellular space, resulting in increased diffusivity and reduced directionality (FA) 3 . Although CC is a good example of NAWM, with high concentration of white matter tracts, it was poorly studied in MS patients 1,6 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have shown decrease of the FA values in the NAWM, probably secondary to myelin sheath and axonal destruction 4,[9][10][11] . These abnormalities tend to expand the extracellular space, resulting in increased diffusivity and reduced directionality (FA) 3 . Although CC is a good example of NAWM, with high concentration of white matter tracts, it was poorly studied in MS patients 1,6 .…”
mentioning
confidence: 99%
“…The classic subdivision of the CC was suggested by Witelson, who tried to link the crossing fibers of the related cortical areas 2 . The callosal tracts are frequently affected in patients with multiple sclerosis (MS), which is a demyelinating disease associated with axonal destruction and Wallerian degeneration [3][4][5] . Magnetic resonance (MR) imaging is the gold standard imaging technique for the evaluation of patients with MS. however, there are microstructural pathologic alterations in MS patients that cannot be assessed with conventional MR sequences 1,6 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Acute NMO patients had significantly higher average MDs than controls in the genu of the CC and optic radiation, and significantly lower average MDs in medulla oblongata, internal capsule and thalamus. [64] CC IN SUSAC SYNDROME MRI Susac's syndrome (SS) is a clinical triad of encephalopathy, branch retinal artery occlusion and sensorineural hearing loss. It is sometimes misdiagnosed because of similarities with ADEM and MS.…”
Section: As a Prognosis Indicatormentioning
confidence: 99%